ASSESSMENT OF THE ENVIRONMENTAL SENSITIVITY OF DESERTIFICATION IN SOUTHERN IRAQ, AL-SAMAWA BADIA USING GIS AND RS TECHNIQUES - Ghid Y. S. A.; A. I. Hamad (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was aimed to investigate and evaluates the degree of environmental sensitivity of desertification and to provide solutions, treatments by identifying the elements and indicators that are directly linked to desertification in southern Iraq. GIS technique was used, and mapping of environmentally sensitive areas for desertification. Five important indices including (soil quality index SQI, climate quality index CQI, vegetation quality index VQI, management quality index MQI, and groundwater quality index GWQI) were used. Results showed that the SQI index was varied between high, moderate, and low quality, the VQI index was varied between moderate to low quality, as for the indices of (CQI, MQI, and GWQI), all classifications were within the lower class. This was reflected negatively on the values of environmental sensitivity to desertification (ESAI) and it became in the critical category within the study area. Consequently, the environmental sensitivity to desertification was calculated by excluding the indices of MQI, and GWQI. Four classes were detected (None affected, Potential, Fragile, and Critical) divided into sub-classes (N, P, F3, C1, C3).